“Problem Barometer” as a tool for cooperation of the Society, Power and Business: Switzerland’s experience - SEMIANOVSKYI, V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The objective of the study is to substantiate the need for introducing “Problem barometer” to address the problems of power-community-business cooperation on the participative management principles, enhance the performance of power offices and the civil society, for gradual settlement of difficult problems arising in contemporary society. The working task is to highlight European instruments for the power-community-business cooperation by the Swiss example and substantiate the possibilities of adapting this practice in Ukraine. The cooperation triangle “Community – Power – Business” is built. An extensive review of “Swiss worry” barometer is given. Using this Swiss practice and data from Kyiv International Institute of Sociology for 2014–2019, “Problem barometer” for Ukrainian is constructed. The public concerns measured by this barometer cover war in the east of Ukraine, life standards, economic situation, security in Ukraine, crime, political situation, relations with Russia, environmental problems, renaissance of the Ukrainian nation, relations with EU, annexation of Crimea, international relations, interethnic relations, other. The options “hard to say” and “refuse to answer” are also included. It is stressed that for political parties or deputies Ukrainian “Problem barometer” signals what social problems should come in their focus in time of the cadence. For public institutions “barometer” shows what social problems call for solutions with the government’s involvement. The “barometer” indicators are also important for the business, especially the socially oriented one. For voters “barometer” indicates whether a deputy or a public official is concerned with the needs of the population or his own needs (or needs of party sponsors). This determines the citizens’ trust in the respective institutions. The conclusion is made that the proposed “Problem barometer” (built by analogy with “Swiss barometer”) is an instrument for streamlining the community-power-business cooperation, which makes it more effective.